Overcoming Drought : Adaptation Strategies for Andhra Pradesh - World Bank (The World Bank, 2006)
Using recent advances in modeling climate-related risks and adjusting state of the art catastrophic risk modeling techniques to drought, the study conducts an innovative long-term assessment of drought risks in Andhra Pradesh, India, and suggests strategies to reduce their impact, under several economic, drought management and climate change scenarios. The analysis deepens an understanding of climate risk adaptation strategies, including implications for agricultural and catastrophic risk insurance